Assessment of the physical flood susceptibility of buildings on a large scale – conceptual and methodological frameworks - A. Blanco-Vogt; J. Schanze (Natural Hazards and Earth System Sciences, 2014)
There are various approaches available for assessing the flood vulnerability and damage to buildings and critical infrastructure. They cover pre- and post-event methods for different scales. However, there can hardly be found any method that allows for a large-scale pre-event assessment of the built structures with a high resolution. To make advancements in this respect, the paper presents, first, a conceptual framework for understanding the physical flood susceptibility of buildings and, second, a methodological framework for its assessment. The latter ranges from semi-automatic extraction of buildings, mainly from remote sensing with a subsequent classification and systematic characterisation, to the assessment of the physical flood susceptibility on the basis of depth–impact functions. The work shows results of the methodology's implementation and testing in a settlement of the city of Magangué, along the Magdalena River in Colombia.